University students' need satisfaction trajectories: A growth mixture analysis. (April 2019) - Gillet, Nicolas; Morin, Alexandre J.S.; Huyghebaert, Tiphaine; Burger, Lucie; Maillot, Axel; Poulin, Aurélie; Tricard, Elodie
Abstract: This study examines trajectory profiles of University students over the course of a University semester defined based on global levels of psychological need satisfaction, as proposed by self-determination theory (SDT). This study also documents the implications of these trajectories for a variety of educational outcomes. A sample of 461 first-year undergraduates completed all measures three times over the course of a University semester. Longitudinal growth mixture analyses (GMA) revealed three distinct need satisfaction trajectories (Low-Decreasing, Moderate-Decreasing, and Moderate-Increasing). The Moderate-Increasing profile was associated with the highest levels of positive affect and effort. In contrast, the Low-Decreasing profile was associated with lower levels of positive affect, effort, and achievement, and higher levels of negative affect than the Moderate-Increasing profile. Highlights: Results revealed three distinct need satisfaction trajectories. The Moderate-Increasing profile relates to the highest levels of positive affect. The Moderate-Increasing profile relates to the highest levels of effort. The Low-Decreasing profile relates to lower levels of positive affect and effort. The Low-Decreasing profile relates to lower levels of achievement.